Effect of gelatin powder, almond shell, and recycled aggregates on chemical and mechanical properties of conventional concrete - Mohammad Hematibahar; Alireza Esparham; Nikolai I. Vatin; Makhmud I. Kharun; Tesfaldet H. Gebre (Structural Mechanics of Engineering Constructions and Buildings, 2023)
The objective of the research is to study the effect of different additives on the conventional concrete. In this term, three types of materials have been added to the concrete: gelatin powder as the binder, recycled aggregates, and almond shell as the fine and coarse aggregates. Several experiments have been made tо determine physical and mechanical properties, such as test for compressive and tensile strengths, for impact loading strength, durability test (water absorption) and deep penetration tests. Moreover, the microstructure results for the new type of concrete have been studied by means of scanning electron microscopy (SEM) and energy-dispersive x-ray spectroscopy (EDXS). The results show that when 70 kg of gelatin powder is added to 1 m3 of concrete, the concrete’s compressive strength and tensile strength are improved more than 22%; during impact loading the first and ultimate cracks are 11 and 129 by numbers, and the first and ultimate cracks’ strength is more than 223 and 2346 J respectively. The durability of sample from concrete with additional gelatin has been improved. SEM results illustrate that the weakness of almond shell concrete is related to cracks and voids between the cement matrix and almond shell. The voids of gelatin concrete are higher than that of conventional concrete. The conventional concrete has smooth crystals, and gelatin concrete has sharp and cubic crystals. EDXS results show that chemical content of these two types of concrete is different: conventional concrete contains silicon, while EDXS results show that chemical content of these two types of concrete is different: conventional concrete contains silicon, while gelatin concrete contains calcium and also C-S-H gel is generated in it.